2015
DOI: 10.1007/s11010-015-2517-9
|View full text |Cite
|
Sign up to set email alerts
|

Bergapten promotes bone marrow stromal cell differentiation into osteoblasts in vitro and in vivo

Abstract: Many recent studies have suggested that bergapten (BP), a class of native compound with numerous biological activities such as anti-resorptive properties, may exert protective effects against postmenopausal bone loss. However, it remains unknown whether BP regulates or improves the osteogenic function of bone marrow stromal cells (BMSCs) in the treatment and prevention of osteoporosis. In our study, BMSCs were cultured in osteogenic induction medium with the addition of BP for 2 weeks and an ovariectomized mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The results showed that Cx43 expression was decreased significantly in the model group in a comparison with the control group, and also the expressions of Runx2, ALP and COLⅠ were decreased significantly in the model group. All these factors are known as the primary regulators or associated factors of the osteogenic differentiation process 43,44 . Osteocytes are mainly originated from BMSCs, where BMSCs firstly undergo lineage differentiation and become pre‐osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that Cx43 expression was decreased significantly in the model group in a comparison with the control group, and also the expressions of Runx2, ALP and COLⅠ were decreased significantly in the model group. All these factors are known as the primary regulators or associated factors of the osteogenic differentiation process 43,44 . Osteocytes are mainly originated from BMSCs, where BMSCs firstly undergo lineage differentiation and become pre‐osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors are known as the primary regulators or associated factors of the osteogenic differentiation process. 43,44 Osteocytes are mainly originated from BMSCs, where BMSCs firstly undergo lineage differentiation and become pre-osteoblasts. Glucocorticoid use could inhibit the differentiation and maturation of pre-osteoblasts through inhibiting Runx2 expression, which followed by a decrease of the expressions of ALP and COLⅠ.…”
Section: Discussionmentioning
confidence: 99%
“…The central role fulfilled by BMP-2 in the activity of furanocoumarins was evident also in young rats treated for 7 consecutive days with bergapten, where it was possible to note a remarkable increase in the bone volume, phosphorylation of SMAD 1/5/8, p38, and ERK, and BMP-2 expression at the level of the tibia. Bergapten modulation of key enzymes in bone health promotion is not limited to the above described proteins, but it involves also the expression of Runt-related transcription factor 2 (RUNX2), modulation of the Wnt/β-catenin pathway, and osteocalcin (noncollagenous protein secreted by osteoblasts) [146,147,148]. Oral administration of bergapten for 3 months to an ovariectomized mouse model (one of the main animal models for studying postmenopausal osteoporosis) resulted in a remarkable decrease in delaying bone loss as shown by analysis of the bone mineral density, separation, and number of trabeculas.…”
Section: Biological Activities Of Furanocoumarinsmentioning
confidence: 99%
“…Earlier, this compound was shown to inhibit diabetes-related osteoporosis via the regulation of the PI3K/AKT, JNK/MAPK, and NF-κB signaling pathways in osteoprotegerin knockout mice and thus to protect trabecular structure and decrease osteoclastogenic differentiation (Li et al 2016b). This coumarin could also promote bone marrow stromal cell differentiation into osteoblasts in vitro and in vivo using a mouse model (Xiao et al 2015). The protective effect of 27 against ovariectomy-induced bone loss was found by distal femur micro-CT scanning, with improvements of bone metabolism parameters such as bone mineral density, trabecular number, and trabecular separation.…”
Section: Osteoporosis and Osteoarthritismentioning
confidence: 99%